Conflicts over host manipulation between different parasites and pathogens: Investigating the ecological and medical consequences. (11th August 2016) - Hafer, Nina
Abstract : When parasites have different interests in regard to how their host should behave this can result in a conflict over host manipulation, i.e. parasite induced changes in host behaviour that enhance parasite fitness. Such a conflict can result in the alteration, or even complete suppression, of one parasite's host manipulation. Many parasites, and probably also symbionts and commensals, have the ability to manipulate the behaviour of their host. Non‐manipulating parasites should also have an interest in host behaviour. Given the frequency of multiple parasite infections in nature, potential conflicts of interest over host behaviour and manipulation may be common. This review summarizes the evidence on how parasites can alter other parasite's host manipulation. Host manipulation can have important ecological and medical consequences. I speculate on how a conflict over host manipulation could alter these consequences and potentially offer a new avenue of research to ameliorate harmful consequences of host manipulation. Abstract : In multiple infections, different interests of parasites in regard to host behaviour and its modification by parasites (i.e. host manipulation) can result in a conflict over host manipulation. In this conflict, one parasite can modify another parasite's host manipulation altering potential ecological and medical consequences of this host manipulation.